1986
DOI: 10.1103/physrevd.34.85
|View full text |Cite
|
Sign up to set email alerts
|

Search for right-handed currents in the decayK+μ+ν

Abstract: The longitudinal polarization of the muon emitted in the decay K + -+ p + v was measured to search for right-handed weak currents in a strangeness-changing process. The 236-MeV/c muons from the decay of stopped K f were identified and were collected by a magnetic spectrometer. The muons were then slowed down in a carbon degrader and were brought to rest in an aluminum target. The muon spins were precessed by a 220-G transverse field, and a muon-spin-rotation technique was employed to measure the muon-spin pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The EDM is even more enhanced if we also allow the R-parity violation, where baryon and lepton numbers are not conserved [165,166,167,168]. If we neglect the one-loop level fermion EDM which is only generated in the presence of soft breaking bilinear R-parity violating interaction [169,170,171,172], the leading CP violation processes are the Barr-Zee type diagram [173,174,175,176,177,178,179] and the CP-odd four-fermion interaction [176,180,181,182]. The majority of CP phases of the R-parity violating couplings are strongly constrained by the current EDM experimental data.…”
Section: Supersymmetric (Susy) Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDM is even more enhanced if we also allow the R-parity violation, where baryon and lepton numbers are not conserved [165,166,167,168]. If we neglect the one-loop level fermion EDM which is only generated in the presence of soft breaking bilinear R-parity violating interaction [169,170,171,172], the leading CP violation processes are the Barr-Zee type diagram [173,174,175,176,177,178,179] and the CP-odd four-fermion interaction [176,180,181,182]. The majority of CP phases of the R-parity violating couplings are strongly constrained by the current EDM experimental data.…”
Section: Supersymmetric (Susy) Modelsmentioning
confidence: 99%
“…with a theoretical uncertainty of about 30%. The isovector nucleon scalar density can be derived in the leading order of the current quark masses in terms of the proton-neutron mass splitting ∆m (0) N as [176,196,333,334,335,336] p|ūu −dd|p = ∆m…”
Section: Cp-odd E-n Interactionmentioning
confidence: 99%
“…where the isospin symmetry was used. The nucleon matrix elements are phenomenologically derived from the anomalous Ward identity [14,[69][70][71][116][117][118][119][120][121]. Using the latest QCD level inputs [122][123][124], we have p|ūiγ 5 u|p = 180, p|diγ 5 d|p = −170, N |siγ 5 s|N = −5.1, N |ciγ 5 c|N = −0.34, and αs 8π N |G a µν G µν a |N = 400 MeV (N = p, n), with about 30% of theoretical uncertainty [17].…”
Section: The P Cp-odd Electron-nucleon Interactionmentioning
confidence: 99%
“…The P, CP-odd e-N interaction is recently attracting attention, since it is generated in the two-Higgs doublet model (2HDM) at the tree level, and has extensively been discussed in the literature [59][60][61][62]. This process is also interesting due to its specific sensitivity to several classes of models such as the supersymmetric models with large tan β [8,[63][64][65][66][67][68] or the R-parity violation [14,[69][70][71][72], as well as the leptoquark models [57,60,[73][74][75] where the s-channel electron-quark interaction is relevant. Since atoms are one of the most accurately measurable systems and give now the world record in the EDM experiments, the study of the contribution of the CP-odd e-N interaction has an inevitable importance in the analysis of the CP violation of these models.…”
Section: Introductionmentioning
confidence: 99%
“…We have therefore good reasons to discuss the one-loop contribution. In this case we have found that similar techniques used in the analysis of the one-loop level P, CP-odd electron-nucleon interaction c-an be applied [26]. Now that we have sufficient motivations, we will analyze in this paper the complete set of RPV contributions to the beta decay at the one-loop level and give its potential observable signature.…”
Section: Introductionmentioning
confidence: 99%